2020
DOI: 10.1021/acsomega.0c00425
|View full text |Cite
|
Sign up to set email alerts
|

Food Additives (Hypochlorous Acid Water, Sodium Metabisulfite, and Sodium Sulfite) Strongly Affect the Chemical and Biological Properties of Vitamin B12 in Aqueous Solution

Abstract: Food additives, such as hypochlorous acid water, sodium metabisulfite, and sodium sulfite, strongly affect the chemical and biological properties of vitamin B 12 (cyanocobalamin) in aqueous solution. When cyanocobalamin (10 μmol/L) was treated with these compounds, hypochlorous acid water (an effective chlorine concentration of 30 ppm) rapidly reacted with cyanocobalamin. The maximum absorptions at 361 and 550 nm completely disappeared by 1 h, and vitamin B 12 activity was lost. There were no significant chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, a high volume of this agent has been found to cause a significant reduction in vitamin C in vegetables. However, more research is needed to understand its effects on vitamin B 12 or other components (Kamoto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high volume of this agent has been found to cause a significant reduction in vitamin C in vegetables. However, more research is needed to understand its effects on vitamin B 12 or other components (Kamoto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfite is widely used as food additives and anti‐browning, but the mechanism of sulfite with foods is not clear yet. Recent study has reported that (bi)sulfite cannot significantly alter the properties of vitamin B 12 (cyano‐cobalamin) in food, but a small amount of sulfite‐cobalamin complex is formed, indicating the interaction between sulfite and cobalt in B 12 [202] …”
Section: Discussionmentioning
confidence: 99%
“…Recent study has reported that (bi)sulfite cannot significantly alter the properties of vitamin B 12 (cyano-cobalamin) in food, but a small amount of sulfite-cobalamin complex is formed, indicating the interaction between sulfite and cobalt in B 12 . [202] Recently, (bi)sulfite is growing attention as a precursor of SO 4 *À radical for expelling MPs from water. However, metal/ (bi)sulfite system has limitation to produce the SO 4…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylaxis was not reported in the phase III clinical trials in Japan where vitamin B12 is commonly used as a treatment for ALS [ 7 , 14 , 15 ]. Vitamin B12 has been used to mitigate the immediate sensitivity to bisulfite based on controlled clinical studies and trials of its effectiveness [ 16 18 ]. One event of anaphylaxis was reported in the pharmacovigilance safety review for the first year after edaravone (Radicava ® ) launch [ 8 ].…”
Section: Discussionmentioning
confidence: 99%